A gas-hydrate related BSR on the W-Svalbard margin: distribution, geological control and formation mechanisms - Vevik, Kristine (Universitetet i Tromsø, 2011)
A widespread bottom-simulating reflection (BSR) defining the base of the gas hydrate stability zone (BGHSZ) exists on seismic data from the western Svalbard margin, including the Vestnesa Ridge, which is a mounded and elongated sediment drift NW of Svalbard to the north of the Molloy Transform. The BSR stretches from the continental slope to within few km of the mid-oceanic ridge system thereby shoaling due to an increase in heat flow over the juvenile oceanic crust, which cools off in eastward direction. The interpretation of a BSR leads to the subdivision into three regions based on distribution and geological setting, namely the Vestnesa Ridge, the continental slope and the Molloy Transform Fault (MTF), where potential gas hydrate occurrences comprise an area of ~2700 km2. The BSR occurrence and inferred hydrate accumulation zone is bound by impermeable glacial debris-flow (GDF) deposits on the upper continental slope, the Knipovich Ridge and MTF to the south and the Molloy Ridge to the west. Enhanced reflections beneath the BSR indicate the presence of significant amounts of free gas. The crest of the Vestnesa Ridge at water depth between 1200-1500 m is pierced with fluid-flow features, but they are absent on the flanks of the ridge, where hydrate-bearing sediments effectively reduce the permeability of the sediments. Thus, fluids are forced to migrate laterally upwards along the GHSZ towards the crest in this topographically controlled system. The vigorous flow of fluids at the crest disrupts the BSR, causing it to shoal locally in vicinity of fluid-flow features. The fluid-flow features are often connected to deep-seated faults indicating a deep hydrocarbon gas supply, which is corroborated by hydrate-stability modeling suggesting a larger fraction of thermogenic hydrocarbons involved in hydrate formation. In addition to that, the combination of high heat flow, tectonic activity, a thick sedimentary cover and a shallow maturation window suggests that the free-gas/gas-hydrate system at the Vestnesa Ridge is ...